Contribution of autophagy machinery factors to HCV and SARS-CoV-2 replication organelle formation - Twu, Woan-Ing; Lee, Ji Young; Kim, Heeyoung; Prasad, Vibhu; Cerikan, Berati; Haselmann, Uta; Tabata, Keisuke; Bartenschlager, Ralf (Cell reports, 2021)
Positive-strand RNA viruses replicate in close association with rearranged intracellular membranes. For hepatitis C virus (HCV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), these rearrangements comprise endoplasmic reticulum (ER)-derived double membrane vesicles (DMVs) serving as RNA replication sites. Cellular factors involved in DMV biogenesis are poorly defined. Here, we show that despite structural similarity of viral DMVs with autophagosomes, conventional macroautophagy is dispensable for HCV and SARS-CoV-2 replication. However, both viruses exploit factors involved in autophagosome formation, most notably class III phosphatidylinositol 3-kinase (PI3K). As revealed with a biosensor, PI3K is activated in cells infected with either virus to produce phosphatidylinositol 3-phosphate (PI3P) while kinase complex inhibition or depletion profoundly reduces replication and viral DMV formation. The PI3P-binding protein DFCP1, recruited to omegasomes in early steps of autophagosome formation, participates in replication and DMV formation of both viruses. These results indicate that phylogenetically unrelated HCV and SARS-CoV-2 exploit similar components of the autophagy machinery to create their replication organelles.